Tertiarization in Chile: Cultural inequality and occupational structure - Modesto Gayo; María Luisa Méndez; Berta Teitelboim (CEPAL Review, 2016)
Tertiarization, or the shift to service economies with an increasing prevalence of non-manual occupations, has been identified as a central phenomenon in contemporary societies. With the purported numerical and political decline of traditional working-class sectors, the middle class has come to be seen in recent decades as the dominant one. This understanding of the way society has evolved has gone along with a growing interest in forms of social differentiation other than the occupational one of industrial societies, including cultural differentiation. This paper briefly reconstructs the debate and shows that while there may have been growth in non-manual occupations, prompting the notion of a progressive shift towards a middle-class society, some important findings make it difficult simply to accept the claim that Chile has become this kind of mesocratic society.